CHARACTERISTICS, METHODS AND CHALLENGES OF TRANSLATING LAW TERMINOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The current article discusses basic problems concerning translation in general, and issues related to translating law documents and terminology. The article includes some real life examples from Uzbek language and English language, and data are given in the form of a table, and sample translations from reliable sources.